Exploring the Preparedness and Competence Level of Pre-service TVET Teachers Using Knowledge, Skills, and Attitude Model - Estubio, Maricris; Sarsale, Melvin (Journal of Technical Education and Training, 2024)
The full implementation of the K-12 curricula and increasing enrolment in TVET institutions in the Philippines urges higher education institutions to provide quality pre-service teacher education continuously. This paper explored the preparedness level of pre-service TVET teachers in terms of specialized courses taken, training certifications attained, and length of course program-related training attended. This paper also determined the competence level of pre-service teachers in select TVET learning areas using the knowledge, skills, and attitude model. Using a descriptive survey design, the researchers administered a validated instrument among the 143 pre-service teachers enrolled in a Philippine university offering a TVET teacher training program. Findings revealed that most pre-service teachers specialized in cookery, cosmetology, carpentry and masonry, basic electricity, drafting, plumbing, and electronics. Only a few had attended course program-related training and attained TVET training certification levels. Findings revealed pre-service teachers perceived competence in knowledge, skills, and attitude in the select TVET learning areas. However, their level of competence varied from each TVET learning area, which calls for a pre-service teaching enhancement program to improve the competency levels of pre-service TVET teachers.